Ethical decision-making in the therapeutic space : a psychoanalytic view - Silove, Melanie (Rhodes University, Faculty of Humanities, Department of Psychology, 2009)
This study examined the ethical decision-making process as it transpired in the everyday context of the therapeutic space. In-depth interviews explored the subjective experiences of six South African psychologists, practicing as psychoanalytic psychotherapists, and their efforts to resolve real-life ethical dilemmas. The theoretical framework used to interpret the data subsumed professional literature in psychology on principle-based ethical decision-making as well as contemporary psychoanalytic debates on the phenomenon of countertransference enactments. A review of ethics codes, survey research and seminal decision-making frameworks suggests that ethical dilemmas have traditionally been resolved by recourse to an objective and impartial "principle ethics" perspective. Empirical evidence shows, however, that logical thinking and the rational application of codes, principles and standards are often insufficient to secure ethical action. The establishment of reflective space and the core theoretical notion of "ethical decision-making enactments" were proposed in order to address the subjective, irrational and unconscious dimension of professional decision-making. This study used a broadly hermeneutic research method which transformed participants"Ÿ descriptions of engagement with real-life dilemmas into a psychoanalytically informed interpretive account of ethical decision-making. Twelve aspirational ethical principles were found to guide participants"Ÿ daily analytic work. Beneficence was the principle most strongly identified with and nonmaleficence was the most neglected ethical principle. Unprocessed countertransference responses were shown to drive earlier prereflective phases of the ethical decision-making process. Mature ethical judgment was predicated upon the retrospective analysis of enactment phenomena. Dissatisfaction was expressed by all participants with regard to the role of professional resources in aiding the resolution of stressful ethical dilemmas. Risk factors for compromised professional decision-making included the paucity and perceived irrelevance of postgraduate ethics training, supervisory failure to confront the ethical and countertransference dimensions of common dilemmas and professional isolation. Rather than eliciting the hope of emotional support and greater insight, professional resources on the contrary mostly appeared to induce anxiety, mistrust and fearfulness. Based on the data and the literature, a pragmatic psychoanalytically informed ethical decision-making model was finally generated. The model, which considers both principle ethics as well as countertransference phenomena, offers a preliminary contribution to professional dialogue on the development and evaluation of empirically based decision-making frameworks. Practical recommendations are made for both the revision of the current South African ethics code and for improving the postqualifying ethics education of psychoanalytic practitioners and supervisors. The limitations of the data are discussed and directions for future research initiatives are proposed.
Keywords: Decision making -- Moral and ethical aspects; Psychotherapy -- Moral and ethical aspects; Psychotherapists -- Professional ethics